Novel Biomarkers in Cardiovascular Disease: A Review - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2010)
BACKGROUND: The investigation of novel circulating serum and plasma biomarkers in patients with cardiovascular disease has been accelerating at a remarkable pace. New markers or tests are often presented too early to the medical profession, potentially leading to overuse and, thus, extra burden and costs to patients, the healthcare industry, and the economy. The challenge for clinicians and medical researchers is how to optimally apply existing and new markers/tests.CONTENT: Biomarkers are biological parameters that can be objectively measured and quantified as indicators of normal biologic processes, pathogenic processes, or responses to a therapeutic intervention. Typically thought of as disease process screening, diagnosing, or monitoring tools, biomarkers may also be used to determine disease susceptibility and eligibility for specific therapies. Cardiac biomarkers are protein components of cell structures that are released into circulation when myocardial injury occurs. They play a pivotal role in the diagnosis, risk stratification, and treatment of patients with chest pain and suspected acute coronary syndrome (ACS) as well as those with acute exacerbations of heart failure.SUMMARY: Active investigation has brought forward an increasingly large number of novel candidate markers but few have withstood the test of time and become integrated into contemporary clinical care because of their readily apparent diagnostic, prognostic, and/or therapeutic utility. With regard to the more novel biomarkers, careful thought is needed with regard to the appropriate target populations for discovery and validation, as well as the criteria used to sort out the contenders from the pretenders.KEYWORDS: biomarker, cardiovascular disease, atherosclerosis, acute myocardial infarction, heart failure, risk stratification, diagnosis, prognosis